Learning Energy Changes Based on Project-Based Learning (PJBL) in Elementary School - Mariana Mariana; Marlina Marlina (Universitas Tanjungpura, 2022)
This study aims to improve knowledge and understanding of energy changes in students. Each individual or group does not know exactly where the material will be given when starting the learning process from easy to difficult, which is effective, appropriate, and not difficult to improve abilities and knowledge thoroughly and cooperatively through project based learning (PjBL). The method used is Classroom Action Research (CAR). Data collection with CAR was administered in fifth grade which amounted to 68 students in elementary school. There were 52 students in Cycle I passed with a percentage of 72%. The students who have not passed amounted to 16 students with a percentage of 28%. In Cycle II, 68 students with a percentage of 100%. The implementation of PJBL Model, understanding of Energy Changes in science learning can be accepted because there is a gradual trial of direct trials, and one of the students are given a wide opportunity to conduct a smaller and effective discussion. If there is a difficulty for students during learning, they can provide information to each other through questions and answers and look for references in other resources.